Theory and practice of innovation development in the banking sector - Zaleska, Małgorzata; Kondraciuk, Przemysław (Teoria i praktyka rozwoju innowacji w sektorze bankowym, 2019)
The aim of this article is to systematise the approach to innovation in the economic theory and to define the indicators used to measure the innovativeness of world economies. The considerations are focused on innovation in the banking sector as it is one of the most innovative sectors worldwide. The identification of the stages of innovation development in this branch is worth emphasising, along with the description of its economic and legal determinants
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 2, s. 76-87
Keywords: economic theory of innovation; innovations in banking industry; banks; FinTechs; start-up; innowacje w teorii ekonomii; innowacje w bankowości; banki